Efficacy and Safety of Plasma Exchange Combined with Hemoperfusion in the Treatment of Organophosphorus Poisoning: A Meta-Analysis - Yao, Zhuan'e; Wang, Pengbo; Fu, Qinjuan; Song, Qiong; Wang, Wei; Liu, Ai; Zhang, Peng (Blood purification, 2023)
Introduction: The aim of the study was to systematically evaluate the efficacy and safety of plasma exchange combined with hemoperfusion in the treatment of organophosphorus poisoning. Methods: PubMed, Embase, the Cochrane Library, China National Knowledge Internet, Wanfang database, and Weipu database were searched for articles about this subject. Literature screening and selection were conducted in strict accordance with the inclusion and exclusion criteria. Results: 14 randomized controlled trials with 1,034 participants were included in this meta-analysis study, including 518 cases in plasma exchange combined with hemoperfusion group (the combination treatment group) and 516 cases in hemoperfusion group (the control group). Compared with the control group, the combination treatment group was associated with a higher effective rate (relative risk [RR] = 1.20, 95% confidence interval [CI] [1.11, 1.30], p < 0.00001) and lower fatality rate (RR = 0.28, 95% CI [0.15, 0.52], p< 0.0001); reduced TNF-α (standardized mean difference [SMD] = −1.95, 95% CI [−2.42, −1.48], p < 0.00001), IL-6 (SMD = −1.94, 95% CI [−3.08, −0.80], p = 0.0009), and C-reactive protein (CRP) (SMD = −1.94, 95% CI [−2.86, −1.03], p < 0.0001); shorten coma time (SMD = −1.99, 95% CI [−2.75, −1.24], p < 0.00001), recovery time of cholinesterase activity (SMD = −1.71, 95% CI [−1.90, −1.53], p < 0.00001), and hospital stay (SMD = −1.29, 95% CI [−1.59, −0.98], p < 0.00001). The incidence of complications in the combination treatment group such as liver and kidney damage (RR = 0.30, 95% CI [0.18, 0.50], p < 0.00001), pulmonary infection (RR = 0.29, 95% CI [0.18, 0.47], p < 0.00001), and intermediate syndrome (RR = 0.32, 95% CI [0.21, 0.49], p < 0.00001) was lower than that in the control group. Conclusions: The current evidence suggests that the combination of plasma exchange with hemoperfusion therapy can reduce the mortality of patients with organophosphorus poisoning, shorten the recovery time of cholinesterase activity and the time of coma, reduce the average length of hospital stay, and reduce the levels of IL-6, TNF-α, and CRP, but high-quality randomized double-blind controlled trials are still required to confirm the current findings in the future.